Biomass activated carbon-decorated spherical β-Ni(OH)2 nanoparticles for enhanced hydrogen production from sulphide wastewater. (December 2020) - Sekar, Sankar; Lee, Sejoon; Kim, Deuk Young; Preethi, V.; Kalirajan, K.M.; Sutha, S.; Saravanan, S.; Therli, Anirudh; Roy, Mahuya; Jagannathan, K.
Graphical abstract: Abstract: Aiming at demonstrating the highly-efficient wastewater treatment via photocatalytic hydrogen production, the nickel hydroxide-anchored biomass activated carbon (NH-AC) nanocomposites were synthesized through the facile sol-gel method followed by the ultrasonication process. The NH-AC nanocomposites exhibited an aggregated nanostructure with the large surface area of 75.02 m 2 /g. For the sulphide wastewater treatment, the nanocomposites showed the enhanced hydrogen production rate of 420 mL/h. Such a superb photocatalytic reaction for NH-AC can be ascribed to the synergic effects from both the high porosity of nickel hydroxide and the high electrical conductivity of activated carbon. These results depict that the NH-AC nanocomposites possess a great potential for photocatalytic hydrogen production from the wastewater.